Evaluation Of Speedboat Patterns Mooring At UPTD LLASDP Wharf, West Tanjung Jabung Regency, Jambi Province - Purboyo Purboyo; Driaskoro Budi Sidharta; Adira Balqis Saputri (IWJ : Inland Waterways Journal, 2022)
UPTD LLASDP Port is a port located on Jl. Asia, Tungkal Ilir, West Tanjung Jabung Regency, Jambi which serves 3 route routes, namely Inter-Province, Inter-Regency, and Inter-Regency. In its application, the mooring pattern greatly affects the up and down activities of passengers at the pier. However, according to the existing conditions, the UPTD LLASDP Pier of West Tanjung Jabung Regency has not implemented a mooring pattern system so that ships that will moor at the Pier are still mooring carelessly without regard to the mooring pattern. This has an impact This is bad for passengers and the goods they carry, passengers who want to board the ship often find it difficult to board because of the irregular position of the ship's berth causing passengers and goods to fall into the river when loading and unloading goods occurs at the dock. The aims of this study are as follows: 1) To determine the existing conditions at the UPTD LLASDP Pier, especially when the ship will moor at the Pier. 2) To find out how the arrangement of the mooring pattern at the pier to suit the situation and conditions that are feasible to support the smooth activity of the pier. 3) To find out whether theactivities operationalas well as the condition of the pier in the passengers' boarding and disembarkation activities in the current condition are balanced with the services of port officers. The research methodology used is direct observation in the field (field research), interviews (Interview), literature/documentation (literature) and institutional. Then to analyze this, it is guided by Soedjono Kramadibaratha's Theory in the Port Planning book. The analysis used is the analysis of the mooring capacity of the ship according to the mooring pattern system (elongated, perpendicular and angled). The results of this study are 1) The capacity of the speedboat that can be moored at the UPTD LLASDP Wharf with a mooring pattern lengthwise to the pier, which is as many as 19 ships. 3) Capacity speedboat to mooring at Pier UPTD LLASDP with mooring system angled toward the dock as many as five ships (for an angle of 30°),7 Ships (to an angle of 45°),9 Ships (to an angle of 60°),19 ships (for angle 75°).This states that it is not necessary to increase the length of the pier because the mooring capacity has sufficed the maximum capacity of ships mooring simultaneously according to the ship's arrival and departure schedules, but there must be arrangements for the mooring pattern of ships and the need for placement of officers to regulate the mooring system at the pier.